Dampak Hospitalisasi Pada Anak Prasekolah di Ruang Anggrek Badan Rumah Sakit Umum Daerah Kabupaten Tabanan - Desak Gede Yenny Apriani; Desak Made Firsia Sastra Putri (Jurnal Kesehatan Medika Udayana, 2021)
Introduction: Hospitalization is a crisis that occurs in children when they are sick and hospitalized. Pre-school children who undergo hospitalization try to adapt to the hospital environment so that it will be a stressor for both children and parents which can cause anxiety. The reactions shown by pre-school children who underwent hospitalization were rebellious, issued inappropriate words, and were less cooperative when nursing actions were carried out. The purpose of this study was to identify the impact of hospitalization on pre-school children (aged 3-6 years) in the Anggrek Room of the Regional General Hospital of Tabanan Regency. Methods: This research is a quantitative descriptive study using a cross sectional approach, respondents were selected by purposive sampling with a sample of 30 pre-school children using an observation sheet. Results: This study shows that the description of the impact of hospitalization on pre-school children in the Anggrek Room is in the high category of 19 respondents (63.3%) and in the low category of 11 respondents (36.7%). It was also found that most of those who were treated were aged 3 years as many as 14 respondents (47.6%), male sex as many as 17 (56.7%), most of whom are only children (50%), have parents, most of whom have high school education (63.4%), some have undergone hospitalization (50%), and some with chronic disease (50%). Conclusion: The impact of hospitalization on school children (aged 3-6 years) in the Orchid Room of the Regional General Hospital of Tabanan Regency is in the high category.